Implementação de Sistemas de Eficiência Energética nos Tratamentos Térmicos - Luísa Maria Videira Morais (2017)
This project is based on an energy efficiency analysis of TRATERME company. The objective is to develop a methodology to optimize the production process related to energy consumption. For this purpose, the influence of some variables of the heat treatment processes - treatment time, furnace temperature variation, weight of the load and type of treatment in the production line - will be studied. It is intended to create a control measure that allows the evaluation of deviations and a methodology to identify the best time to start production and which furnace is the most appropriate.